Direct growth of Cnms on stainless steel (effect of surface roughness) - Muhammad Izzhar Abd Malik (School of Material Engineering, University Malaysia Perlis, 2016)
The effect of surface roughness towards the direct growth of surface roughness on stainless steel S316 has been investigated. Carbon nanomaterials (CNMs) were grown on a surface of a stainless steel 316 pellets at the size of 5.5 mm thickness and 12.7 mm diameter by chemical vapor deposition. The process at 800C for 30 min at the flow rate of acetylene gas at 200 ml/min. The carrier gas used is argon gas. The AFM and SEM-EDX have been used to characterize for morphological and elemental analysis. It is demonstrates that CNMs growth is directly affected by the surface roughness of stainless steel. The grit of 80 is the best surface roughness to produce CNMs on the metal substrate 316. The uniformity of diameter roughness at 80 has produced the greater uniform coverage diameter carbon in range of 150 - 220 nm respectively, while grit of 800 and 1200 has created the non-uniformity coverage of carbon which in the range of 180 - 189.99 nm.